Proceedings of the symposium on mountain meteorology - Rasmussen, J. L., author; Reiter, Elmar R., author; Department of Atmospheric Science, Colorado State University, publisher (Colorado State University. Libraries, 1967)
The symposium was held on 26 June 1967 in Fort Collins, Colorado.
Keywords: Meteorology -- Congresses; Weather -- Effect of mountains on